Decentralized Composting of Food Waste: A Perspective on Scientific Knowledge - Sánchez, Antoni (Frontiers in Chemical Engineering, 2022)
Composting has demonstrated to be an effective and sustainable technology to treat a wide variety of organic wastes. The process is based on the microbial decomposition of organic matter under aerobic conditions to obtain compost: an organic amendment that can be safely used in agriculture and other applications because of its stable and mature characteristics. With a proper management, compost also contains macro and micronutrients that are very useful for crops. Among the composted wastes, the organic fraction of municipal waste, wastewater sludge, agricultural and farm wastes are the most commonly used. One particular aspect of composting is the variety of technological options that can be used for composting, from full-scale plants to individual composters. In this sense, the interest in composting at home or community scale is exponentially growing in recent years, as it permits the self-management of organic wastes and obtaining a compost that can be used by the own producer. However, some questions about the quality of the obtained compost, the environmental impact of home composting and the feasibility of vermicomposting are stage in an early stage of this development and knowledge. In this review, the main points related to home and community composting are analysed in detail according to the scientific current knowledge and highlighting their advantages and possible drawbacks.